Strengthening Students' Character through the Curriculum of Love in Islamic Religious Education - Tyas Ayu Farah Dina; Hany Lidya Putri; Nanang Ilham Fatih; Muntaqo Fadli; Rodianto (IAIN Batusangkar, 2026)
This study is motivated by the increasing character crisis among students in the modern era, which is reflected in bullying, intolerance, declining social empathy, and moral degradation within educational environments. These conditions indicate that Islamic Religious Education (PAI) has not fully succeeded in developing students’ affective, moral, social, and spiritual dimensions because learning practices still tend to emphasize cognitive achievement. Therefore, this study aims to analyze the concept of the Curriculum of Love in education, examine character strengthening from the perspective of Islamic education, and describe its implementation in Islamic Religious Education learning. This study employed a qualitative approach with a library research design. Data were collected from books, scientific articles, policy documents, and relevant literature related to the Curriculum of Love, character education, and Islamic Religious Education. The data were analyzed using the Miles and Huberman model, including data condensation, data display, and conclusion drawing, while source triangulation was used to ensure data validity. The findings reveal that the Curriculum of Love strengthens students’ character through four core values, namely compassion, empathy, tolerance, and social responsibility, which are implemented through humanistic learning relationships, teacher role modelling, value habituation, parental collaboration, and meaningful learning environments. The study also found that the integration of peace-oriented educational media and digital pedagogical innovation supports the internalization of Islamic values and the development of respectful, disciplined, and socially responsible behavior among students. This study concludes that the Curriculum of Love offers a relevant and transformative approach for strengthening students’ character in Islamic Religious Education by balancing cognitive, affective, spiritual, and social dimensions. The findings imply that Islamic Religious Education teachers need to develop more humanistic, compassionate, and value-oriented learning practices to address contemporary character crises among students. Keywords: Curriculum of Love; Character Education; Islamic Religious Education.